Composition of catches of Bagan boats on KM.NF vessels in UPTD PPW II PPI Air Bangis Pasaman Barat Sumatera Barat - Fathonah, Nur; Bustari, Bustari; Zain, Jonny (Science, Technology, and Education Care, 2025)
The research was conducted from January 01 to January 31, 2024, at the UPTD PPW II PPI Air Bangis, Pasaman Barat, West Sumatra Province. This study aimed to determine the target catch using the boat lift net fishing gear on the KM.NF vessel at the UPTD PPW II PPI Air Bangis Pasaman and to analyze the catch on Pini and Mentawai islands using the boat lift net fishing gear on the KM.NF vessel at the UPTD PPW II PPI Air Bangis Pasaman. The method used in this research was a survey method, which was analyzed descriptively. This boat lift net fishing gear utilizes light as a tool to attract the attention of fish, inviting them to approach the gear or enter the desired catch area, known as the catchable area. The boat lift net can be categorized into lifting nets based on its operational method. The use of light as an aid in boat lift nets continues to evolve, with variations ranging from stationary to floating boat lift nets. The fishing grounds for boat lift net vessels are located around the Mentawai and Pini islands, approximately 70 miles from the waters, with a depth of about 50 m. Fishing activities occur during the tide's ebb and flow at night. The process of retrieving the catch is done when the speed of the ebb or flow begins to weaken, ensuring more conducive conditions for fishing operations. The use of fishing gear is not